Advanced ultrasonic testing of complex shaped composite structures; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Dolmatov D. O. Dmitry Olegovich; Zhvyrblya V. Yu. Vadim Yurievich; Filippov G. A. German Alekseevich; Salchak Ya. A. Yana Alekseevna; Sedanova E. P. Elizaveta Pavlovna (2016, 2016)
Title screen